Offshore Profit Shifting and Aggregate Measurement: Balance of Payments, Foreign Investment, Productivity, and the Labor Share - Guvenen, Fatih; Mataloni, Raymond J.; Rassier, Dylan G.; Ruhl, Kim J. (American Economic Review, 2022)
We show how offshore profit shifting by US multinational enterprises affects several key measures of the US economy. Profits shifted out of the United States grew rapidly from the mid-1990s to 2010 and have since waned. From 1982–2016, on average, 38 percent of income attributed to US direct investment abroad is reattributable to the United States. We find that adjusting for profit shifting shrinks the trade deficit, decreases the return on US foreign direct investment abroad, boosts productivity growth rates in the late 1990s and early 2000s, and lowers labor’s share of income. (JEL E23, E25, F14, F23, H25, H87, L25)